Mitochondrial DNA sequence variation in human evolution and disease. - Wallace, D C (1994)
Germ-line and somatic mtDNA mutations are hypothesized to act together to shape our history and our health. Germ-line mtDNA mutations, both ancient and recent, have been associated with a variety of degenerative diseases. Mildly to moderately deleterious germ-line mutations, like neutral polymorphisms, have become established in the distant past through genetic drift but now may predispose certain individuals to late-onset degenerative diseases. As an example, a homoplasmic, Caucasian, tRNA(Gln) mutation at nucleotide pair (np) 4336 has been observed in 5% of Alzheimer disease and Parkinson disease patients and may contribute to the multifactorial etiology of these diseases. Moderately to severely deleterious germ-line mutations, on the other hand, appear repeatedly but are eliminated by selection. Hence, all extant mutations of this class are recent and associated with more devastating diseases of young adults and children. Representative of these mutations is a heteroplasmic mutation in MTND6 at np 14459 whose clinical presentations range from adult-onset blindness to pediatric dystonia and basal ganglial degeneration. To the inherited mutations are added somatic mtDNA mutations which accumulate in random arrays within stable tissues. These mutations provide a molecular clock that measures our age and may cause a progressive decline in tissue energy output that could precipitate the onset of degenerative diseases in individuals harboring inherited deleterious mutations.